16(x+3)=36(x+2)

Simple and best practice solution for 16(x+3)=36(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16(x+3)=36(x+2) equation:


Simplifying
16(x + 3) = 36(x + 2)

Reorder the terms:
16(3 + x) = 36(x + 2)
(3 * 16 + x * 16) = 36(x + 2)
(48 + 16x) = 36(x + 2)

Reorder the terms:
48 + 16x = 36(2 + x)
48 + 16x = (2 * 36 + x * 36)
48 + 16x = (72 + 36x)

Solving
48 + 16x = 72 + 36x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36x' to each side of the equation.
48 + 16x + -36x = 72 + 36x + -36x

Combine like terms: 16x + -36x = -20x
48 + -20x = 72 + 36x + -36x

Combine like terms: 36x + -36x = 0
48 + -20x = 72 + 0
48 + -20x = 72

Add '-48' to each side of the equation.
48 + -48 + -20x = 72 + -48

Combine like terms: 48 + -48 = 0
0 + -20x = 72 + -48
-20x = 72 + -48

Combine like terms: 72 + -48 = 24
-20x = 24

Divide each side by '-20'.
x = -1.2

Simplifying
x = -1.2

See similar equations:

| 8+9g=10g+10 | | 4073.86=1960+150.99x | | 2x+2-9x=7x+2 | | 12-5=11 | | 14-3(4f-1)= | | -2(5)-5y=20 | | F(1)=1*(1*1)-1 | | -5+5(c+4)= | | -2(0)-5y=20 | | 75(11+9)= | | -2(-5)-5y=20 | | 9-3(2a-4)= | | 792.50=405+15.50h | | -2(-10)-5y=20 | | ?-13/15=4 | | 8b-6(3x-2)= | | 13-13/15=4 | | F(-1)=-1*(-1*-1)-1 | | 3000=10x+1500 | | 7x+13x-4=4(5x+8) | | 700=.18x+17.43 | | 6+9d= | | 32*20+8(1.5*20)= | | F(-2)=-2*(-2*-2)-1 | | -3(v-5)+8(2v-1)= | | 6+9d-2= | | 32x+8(1.5x)=800 | | 63.83=.10x+3.83 | | 4(4x+5)=18+18-2x+2 | | 11+2y=8+2y+3 | | 4(4x+5)=18+8-2x+2 | | F(-3)=-3*(-3*-3)-1 |

Equations solver categories